PENGARUH KELENGKAPAN PRODUK, TATA LETAK, DAN LOKASI TERHADAP KEPUTUSAN PEMBELIAN PADA TOKO PAKAN TERNAK HERI - Windi Tarisa Januar; Eko Widodo; Ustadus Sholihin (Musytari : Neraca Manajemen, Akuntansi, dan Ekonomi, 2024)
Heri Animal Feed Shop is a shop that operates in the animal feed sector which is located on Jl. Mujair etc. Dadapan Ds. Tawang District. Wates District. Kediri was founded by Mr Heri Mujiono in 2006. This research was conducted with the aim of finding out, explaining and proving the hypothesis that product completeness, layout and location influence purchasing decisions at the Heri Animal Feed Shop. The research method used is causal associative quantitative, where the sampling method is accidental sampling using a questionnaire and Likert scale. Where the population of this study is all unknown consumers of the Heri Animal Feed Shop. The sample for this study consisted of 385 respondents using the Cochran formula. The analysis method used is multiple linear regression using SPSS 25 for Windows. This research shows that product completeness, layout and location partially have a positive influence on purchasing decisions at the Heri Animal Feed Shop as evidenced by the significance of the t test value of 0.000 < 0.05. And in the f test, product completeness, layout and location have a simultaneous influence on purchasing decisions with a significance value of 0.000 <0.05.